2014
DOI: 10.1371/journal.pone.0097802
|View full text |Cite
|
Sign up to set email alerts
|

Associations of All-Cause Mortality with Census-Based Neighbourhood Deprivation and Population Density in Japan: A Multilevel Survival Analysis

Abstract: BackgroundDespite evidence that neighbourhood conditions affect residents' health, no prospective studies of the association between neighbourhood socio-demographic factors and all-cause mortality have been conducted in non-Western societies. Thus, we examined the effects of areal deprivation and population density on all-cause mortality in Japan.MethodsWe employed census and survival data from the Japan Public Health Center-based Prospective Study, Cohort I (n = 37,455), consisting of middle-aged residents (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 36 publications
7
84
1
Order By: Relevance
“…Low neighbourhood SES is shown to predict all-cause mortality [16, 17, 24], mortality after myocardial infarction [25], and the risk of mortality among adults with cancers [26]. The results of our study extend the above-mentioned findings by reporting the effects of neighbourhood deprivation on all-cause mortality among patients with atrial fibrillation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Low neighbourhood SES is shown to predict all-cause mortality [16, 17, 24], mortality after myocardial infarction [25], and the risk of mortality among adults with cancers [26]. The results of our study extend the above-mentioned findings by reporting the effects of neighbourhood deprivation on all-cause mortality among patients with atrial fibrillation.…”
Section: Discussionsupporting
confidence: 79%
“…For example, neighbourhood SES has been found to be associated with overall health [13], cardiovascular health [14, 15], and all-cause mortality [16, 17]. A previous study found an association between neighbourhood SES and hospitalization of atrial fibrillation patients in women that no longer remained significant after adjustment for individual factors [18].…”
Section: Introductionmentioning
confidence: 99%
“…For deprivation, we used the Kyuson-level deprivation index, devised by Nakaya (2011), which is a composite indicator consisting of weighted sums of several poverty-related census-based variables, such as proportion of old couple households, proportion of old single households, proportion of single-mother households, proportion of rented houses, proportion of sales and service workers, proportion of agricultural workers, proportion of blue collar workers, and the unemployment rate, from the 1995 population census. Details of the deprivation index are described elsewhere (Nakaya, 2011;Nakaya et al, 2014). Residential instability in each neighborhood was defined as the proportion of individuals who had lived in the same municipality for five years or less.…”
Section: Independent Variablesmentioning
confidence: 99%
“…It is well known that area-level socioeconomic conditions have a contextual association with an individual's health outcomes [1][2][3]. Many studies have indicated that area-level deprivation, which re ects various aspects of an area's socioeconomic positions, can affect the health outcomes of its residents, including mortality [4][5][6][7], morbidity [8][9][10][11], mental health [12,13], poor birth outcomes [14][15][16], and health risk behavior [17,18]. The impact of area-level deprivation on health matters for not only public health policies but also macroeconomic and social policies, which are committed to income redistribution, labor market regulations, and other issues related to social welfare.…”
Section: Introductionmentioning
confidence: 99%